Familial disease history and fur color type are associated with urinary tract disease in farmed mink (Neovison vison). (December 2020) - Mundbjerg, Karin; Tolver, Anders; Sebbelov, Ida; Clausen, Tove; Lundfold, Jesper; Hammer, Anne Sofie
Abstract: Mink urinary tract disease (MUTD) and mink fatty liver disease (MFLD) constitute two important disease entities in the mink production associated with sudden mortality and economic loss. Genetic factors or heritability of the diseases have not previously been investigated. Since mortality associated with MUTD and MFLD mainly occurs in the young immature mink, a potential genetic predisposition would rarely be passed on by the mink itself but potentially by relatives. This study aimed to investigate familial aggregation of MUTD and MFLD based on data from four generations of mink on a research farm. The study included a total of 27, 511 mink of brown and black color type with a post mortem prevalence of 0.8% for MUTD ( n = 221) and 0.5% for MFLD ( n = 138) within a year from birth. The prevalence in the color types brown and black were 0.6% and 1.6% for MUTD and 0.5% and 0.7% for MFLD. Family history of MUTD in breeding animals was found to be associated with a significantly higher probability of MUTD leading to mortality in offspring ( p = 0.012, RR = 1.7; CI [1.1–2.4]), however this association was not significant for MFLD ( p = 0.163, RR = 1.5; CI [0.9–2.7]). Mink of the color type black showed significantly higher risk of MUTD (RR = 2.6; CI [2.0–3.3]) and MFLD ( R = 1.6; CI [1.1–2.2]) compared to brown mink. The results indicate that genetic factors may play a role in understanding MUTD and that selective breeding may contribute to reduce mortalities associated with this disease. Highlights: Familial aggregation of mink urinary tract disease on a Danish research farm. Familial aggregation as a tool for breeding healthy farm mink. Fur color as a risk factor in urinary tract disease and fatty liver disease in mink.